Perforin oligomers form arcs in cellular membranes: a locus for intracellular delivery of granzymes. - Metkar, S; Marchioretto, M; Antonini, V; Lunelli, L; Wang, B; Gilbert, R; Anderluh, G; Roth, R; Pooga, M; Pardo, J; Heuser, J; Serra, MD; et al. (2015)
Perforin-mediated cytotoxicity is an essential host defense, in which defects contribute to tumor development and pathogenic disorders including autoimmunity and autoinflammation. How perforin (PFN) facilitates intracellular delivery of pro-apoptotic and inflammatory granzymes across the bilayer of targets remains unresolved. Here we show that cellular susceptibility to granzyme B (GzmB) correlates with rapid PFN-induced phosphatidylserine externalization, suggesting that pores are formed at a protein-lipid interface by incomplete membrane oligomers (or arcs). Supporting a role for these oligomers in protease delivery, an anti-PFN antibody (pf-80) suppresses necrosis but increases phosphatidylserine flip-flop and GzmB-induced apoptosis. As shown by atomic force microscopy on planar bilayers and deep-etch electron microscopy on mammalian cells, pf-80 increases the proportion of arcs which correlates with the presence of smaller electrical conductances, while large cylindrical pores decline. PFN appears to form arc structures on target membranes that serve as minimally disrupting conduits for GzmB translocation. The role of these arcs in PFN-mediated pathology warrants evaluation where they may serve as novel therapeutic targets.